Effect of weight and drop height of hammer on the flexural impact performance of fiber-reinforced concrete. (1st June 2017) - Zhang, Wuman; Chen, Shuhang; Liu, Yingzhou
Abstract: The drop weight test was usually used to evaluate the impact performance of fiber-reinforced concrete. However, there is no uniform parameters about the weight and the drop height of the hammer in the drop weight test. In this paper, the effect of the weight and the drop height of the hammer on the impact performance of steel fiber and polypropylene fiber reinforced concrete was studied. The results show that, for both polypropylene fiber and steel fiber reinforced concrete, the initial impact strength (S i ) and the final impact strength (S f ) exponentially decrease with the increase of the drop height. S i and S f increase with the increase of the drop weight when the impact energy is a constant value in each impact test. However, the damage of the polypropylene fiber reinforced concrete is still a brittle fracture at this condition. The addition of steel fiber improves the ductility and impact resistance of concrete.